2006
DOI: 10.1111/j.1600-0609.2005.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and methylation analysis of the cyclin‐dependent kinase 4 inhibitor (p16INK4A) gene in chronic lymphocytic leukemia

Abstract: These results indicate that genetic alterations of p16 gene are rare events in patients with CLL. The clarification of the role of p16 gene promoter methylation in the pathogenesis and evolution of CLL needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…A methylation frequency of 12% was shown in CLL patients in this study. Few studies reported methylation in 6-18% of CLL patients (Nosaka et al, 2000;Chim et al, 2006a;Tsirigotis et al, 2006;Seeliger et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A methylation frequency of 12% was shown in CLL patients in this study. Few studies reported methylation in 6-18% of CLL patients (Nosaka et al, 2000;Chim et al, 2006a;Tsirigotis et al, 2006;Seeliger et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In CLL patients, methylation was reported in p15 (Nguyen et al, 2001;Chim et al, 2006;Seeliger et al, 2009), p16 (Nosaka et al, 2000;Chim et al, 2006a;Tsirigotis et al, 2006;Seeliger et al, 2009) and DAPK (Katzenellenbogen et al, 1999;Chim et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies in CLL, examined the methylation status of p16, another member of the INK4 family, demonstrating a low frequency [2,6,7]. More recently Chim et al, have shown by MS-PCR, p15 promoter methylation in 36% and p16 in 14% of newly diagnosed Chinese patients with CLL and these abnormalities did not correlate with age, stage, sex, and overall survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…INK4A [96] and p15 INK4B [97] genes have also been described in small proportion of CLL patients, however the clinical significance from these small studies are yet undefined.…”
Section: Methylation Of P16mentioning
confidence: 99%